ANALYSIS OF THE IMPACT OF THE DESCHOOLIZED TRAINING STRATEGY OF THE EXTENSION OF THE TECHNOACADEMY FOR THE DISSEMINATION OF SCIENCE AND TECHNOLOGY IN THE RURAL AREA OF THE TOLIMA DEPARTMENT - Castellanos, S. L.
The mission of the extension of the Tecnoacademia is the dissemination of knowledge in science and technology in the rural areas of the department, with the purpose of reducing the gap of technological inequality between the countryside and city. For this, training programs are carried out that allow rural apprentices to develop research projects training, applied to the automation of agro-industrial processes, implementing industry 4.0 techniques and in coordination with the productive sector. This program of training that will be a case study, was executed in 2020 with young people of the municipalities of the department of Tolima, specifically in 16 municipalities inwhich projects were developed that provided solutions to local problems. The study illustrated in this article was applied to the municipalities of Anzoátegui and Ortega, and their results showed a great interest in the participation, execution and continuity of said projects and commit the apprentices to the training constant in emerging technologies, to be applied in agro-industrial processes that support the economic development of the region.